Graphene / acrylonitrile-based functional high-molecular polymer

Through the aqueous phase suspension polymerization method and the copolymerization modification of graphene, highly water-absorbent and conductive acrylonitrile-based functional polymer materials were prepared, which solved the problems of decreasing polymer or fiber strength and uneven hydrolysis during hydrolysis in the prior art, and achieved efficient polymer modification and performance improvement.

CN119875001APending Publication Date: 2025-04-25CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311382878.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-24
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the prior art, when preparing acrylonitrile-based polymer materials containing carboxylic acid groups, the hydrolysis process can easily lead to problems such as decreasing the strength of the polymer or fiber, uneven hydrolysis, and long process.

Method used

Using the aqueous phase suspension polymerization method, more than 84% acrylonitrile and less than 13% unsaturated olefins with carboxylic acid groups were used, and graphene was added to achieve its uniform dispersion and copolymerization modification, and a polymer polymer with a molecular weight of more than 50,000 and super-absorbent function was prepared.

Benefits of technology

The high water absorption of the polymer is achieved (more than 2 times its own weight), and the polymer can be directly grafted and modified to generate a modified polymer with different functional groups, which has conductive functions, while avoiding the problems of strength drop and unevenness during hydrolysis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a graphene / acrylonitrile-based functional high-molecular polymer. The functional high-molecular polymer comprises a first monomer acrylonitrile accounting for 84%-97% of the total monomer proportion, a second monomer carboxyl-containing unsaturated olefin accounting for 1%-13% of the total monomer proportion, a chain transfer agent accounting for 0.5%-4.5% of the total monomer proportion, graphene accounting for 2%-10% of the total monomer proportion and an initiator accounting for 0.5%-4.5% of the total monomer proportion. According to the preparation method, a water-phase suspension polymerization method is adopted, and a stably dispersed graphene aqueous solution is added into a water-phase suspension, so that graphene is uniformly dispersed and subjected to copolymerization modification in the suspension, and the conductive acrylonitrile-based functional polymer material which is ultrahigh in water absorption and can be directly grafted and modified is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional polymers and preparation thereof, and specifically relates to a graphene / acrylonitrile-based functional high molecular polymer and a preparation method thereof. Background Art

[0002] Acrylonitrile (AN) has a cyano group (-CN) on its side group, so it is a widely used monomer in the synthesis of various organic products such as acrylonitrile fibers, resins and plastics. It is a highly reactive compound containing active vinyl and cyano groups. Acrylonitrile is widely used in the production of polyacrylonitrile fibers and ABS resins. Conventional polyacrylonitrile fibers are prepared by copolymerization of acrylonitrile and methyl acrylate or vinyl acetate. Due to their similarity to wool and their hydrophobicity, they can be used in a variety of textiles. The raw material of carbon fiber, the precursor, is generally a copolymer of acrylonitrile, methyl methacrylate or vinyl acetate and itaconic acid. The content of acrylonitrile is above 90%, and the content of the third monomer itaconic acid is between 0.5% and 3.0%. Under high temperature, the cyano group of the precursor undergoes oxidation and cyclization, and finally forms carbon fibers.

[0003] In addition to the application fields of textiles and carbon fibers, polyacrylonitrile also has some other application fields, such as: modifying some cyano groups into carboxylic acid groups by hydrolysis, and then grafting functional groups to prepare functional polymers or fibers. However, in the current hydrolysis process, the problems encountered are that the polymers or fibers with a high degree of hydrolysis appear "paste-like" and the strength decreases significantly; the fiber hydrolysis is uneven; the process is long and the time is long, and continuous production cannot be formed.

[0004] Graphene is a highly conductive nanomaterial discovered in recent years. As a filler, it can significantly improve the conductivity of polymers. However, the application of graphene in polymers also faces problems of dispersion, compatibility and stability in the polymer matrix. The dispersion and stability of graphene in acrylonitrile-based functional polymers are prerequisites for the preparation of functional polymers.

[0005] In view of the deficiencies in the above processes and in combination with market demand, the present invention has developed and provided a graphene / acrylonitrile-based functional high molecular polymer and a preparation method thereof, which can be used for the modification and development of functional polymers in special fields. Summary of the invention

[0006] The present invention aims at the problems encountered in the current route of preparing carboxylic acid group-containing polymer materials by hydrolyzing acrylonitrile-based polymers or fibers, and provides a graphene / acrylonitrile-based functional polymer and a preparation method thereof. The present invention prepares a polymer having a molecular weight greater than 50,000 and having super water-absorbing function by using an aqueous phase suspension polymerization method to prepare more than 84% acrylonitrile and less than 13% unsaturated olefins with carboxylic acid groups. In addition to the super water-absorbing function, the polymer can also be modified by grafting, cross-linking, etc. to generate modified polymers with different functional groups for use in different fields. The preparation method of the present invention adopts an aqueous phase suspension polymerization method, adds a stably dispersed graphene aqueous solution to an aqueous phase suspension, uniformly disperses the graphene in the suspension, copolymerizes and modifies, and obtains a conductive acrylonitrile-based functional polymer material with super high water absorption and direct grafting modification.

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] The first aspect of the present invention provides a graphene / acrylonitrile-based functional macromolecular polymer, comprising the following components in weight percentage:

[0009] The first monomer acrylonitrile accounts for 84%-97% of the total monomer ratio, the second monomer unsaturated olefin containing carboxyl accounts for 1%-13% of the total monomer ratio, the chain transfer agent accounts for 0.5%-4.5% of the total monomer ratio, the graphene accounts for 2%-10% of the total monomer ratio, and the initiator accounts for 0.5%-4.5% of the total monomer ratio.

[0010] Furthermore, the super absorbent acrylonitrile-based polymer comprises the following components in weight percentage: the first monomer acrylonitrile accounts for 88%-95% of the total monomer ratio, the second monomer carboxyl-containing unsaturated olefin accounts for 2%-10% of the total monomer ratio, the chain transfer agent accounts for 1%-4% of the total monomer ratio, the graphene accounts for 3%-6% of the total monomer ratio, and the initiator accounts for 0.8%-4% of the total monomer ratio.

[0011] Furthermore, the first monomer acrylonitrile has an acrylonitrile content greater than 99.5% and an iron content less than 0.1 mg / kg, and Shanghai Secco acrylonitrile is preferably used.

[0012] Furthermore, the second monomer, the unsaturated olefin containing a carboxyl group, is one or more of acrylic acid, itaconic acid or methacrylic acid.

[0013] Furthermore, the chain transfer agent is an organic substance with a hydroxyl group, preferably one or more of isopropanol, diethylhydroxylamine, and tetrahydroxyporphyrin.

[0014] Furthermore, the initiator is a water-soluble oxidation / reduction system initiator, wherein the types of oxidants include ammonium persulfate (APS), potassium persulfate (KPS), sodium chlorate, hydrogen peroxide, etc.; the types of reducing agents include sodium sulfite, sodium bisulfite, sulfurous acid, ethylenediamine, etc.; the mass ratio of the oxidant to the reducing agent is 1:1 to 1:6.

[0015] Furthermore, the molecular weight of the super absorbent acrylonitrile-based polymer is between 50,000 and 100,000, and the water absorption capacity is more than 2 times of its own weight.

[0016] Furthermore, the super absorbent acrylonitrile-based polymer includes the following components in weight percentage: the first monomer acrylonitrile accounts for 88% of the total monomer ratio, the second monomer itaconic acid accounts for 9% of the total monomer ratio, the chain transfer agent hydroxylamine accounts for 2% of the total monomer ratio, the graphene accounts for 4% of the total monomer ratio, and the initiator composed of ammonium persulfate (APS) and ammonium bisulfite in a mass ratio of 1:4 accounts for 3% of the total monomer ratio.

[0017] The second aspect of the present invention provides a method for preparing the above-mentioned super absorbent acrylonitrile-based polymer, comprising:

[0018] 1) adding acrylonitrile, a first monomer, and a carboxyl-containing unsaturated olefin, a second monomer, into a polymerization kettle after being measured by a flow meter according to the above weight percentage;

[0019] 2) Start the polymerization stirring, keep the temperature at 20°C to 30°C, add the chain transfer agent and pH adjuster, and adjust the pH of the mixed solution to 1.5 to 3.5; then add the initiator, carry out the polymerization reaction at 30-60°C, and control the reaction time to 2-3h to generate an acrylonitrile-based polymer suspension with a carboxylic acid group;

[0020] 3) adding a stably dispersed graphene aqueous solution to the polymer suspension;

[0021] 4) adjusting the pH value of the acrylonitrile-based polymer suspension to between 3.0 and 5.0 using an alkaline solution to terminate the polymerization reaction;

[0022] 5) After the pH of the acrylonitrile-based polymer suspension is adjusted, the polymer forms a filter cake, and the filter cake is dried at 80-150° C. to obtain a super absorbent acrylonitrile-based polymer.

[0023] Furthermore, the concentration of the second monomer carboxylic acid unsaturated olefin in step 1) is in the range of 1 wt% to 13 wt% of the total monomers; preferably in the range of 2% to 10%.

[0024] Furthermore, the total monomer concentration in the polymerization kettle in step 1) is in the range of 6wt% to 25wt%; the preferred concentration range is 8wt% to 20wt%.

[0025] Furthermore, the concentration of the chain transfer agent in step 2) is in the range of 0.5 to 4.5 wt % of the total weight, preferably in the range of 0.8 wt % to 4.0 wt %.

[0026] Furthermore, the initiator in the step 2) is a water-soluble oxidation / reduction system initiator, wherein the types of oxidants include ammonium persulfate (APS), potassium persulfate (KPS), sodium chlorate, hydrogen peroxide, etc.; the types of reducing agents include sodium sulfite, sodium bisulfite, sulfurous acid, ethylenediamine, etc.; the ratio of the initiator to the total monomer is between 0.5 and 4.5 wt%, preferably between 1.0 and 4.0%.

[0027] Furthermore, the pH regulator in step 2) is a regulating system of nitric acid or sulfuric acid and sodium hydroxide, and the pH of the mixed solution is adjusted to be in the range of 1.8 to 3.0.

[0028] Furthermore, the alkaline solution in step 3) is an alkaline solution with a concentration of 1 to 8 wt%, and the alkaline substance can be ammonia water, caustic soda, potassium hydroxide, etc. The alkaline solution adjusts the pH value of the acrylonitrile-based polymer suspension to between 3.0 and 5.0.

[0029] Furthermore, the drying in step 5) is performed by heating and drying with hot air containing nitrogen, and the heating temperature is controlled between 90 and 120°C.

[0030] The preparation method of the present invention adopts an aqueous suspension polymerization process route, wherein the polymerization monomers are added into a polymerization kettle filled with pure water after being metered, and after being kept at a constant temperature to a process value, the pH value of the mixed solution is adjusted to a certain range using nitric acid or sulfuric acid, and an initiator of an oxidation / reduction system is added to initiate polymerization, and after the polymerization of the aqueous suspension is terminated, the monomers are removed, washed with water and dried, and finally the required polymer powder is prepared.

[0031] The carboxylic acid group has strong water absorption and high activity, but the unsaturated olefin containing the carboxylic acid group has a lower reactivity rate than acrylonitrile. Therefore, its conversion rate is relatively low during free radical polymerization. When intermittent polymerization is used, appropriate monomer addition can be used during the polymerization process to ensure its conversion rate and content in the copolymer. When continuous polymerization is used, the component ratio in the copolymer can be controlled by stably controlling the feed ratio of the polymerization kettle, and the residual monomers are returned to the polymerization kettle after metering to participate in the polymerization reaction. The concentration range of the second monomer carboxylic acid unsaturated olefin to the total monomer is between 1wt% and 13wt%. The total monomer concentration range in the polymerization kettle is between 6wt% and 25wt%. At the same time, since the carboxylic acid group itself is highly active and easily oxidized by heat, the drying temperature control range of the polymer is between 80 and 150°C when the polymer is dried by hot air. The prepared polymer powder has a water absorption capacity greater than 2 times (relative to its own mass), and can be directly chemically grafted without hydrolysis.

[0032] In the above-mentioned super absorbent acrylonitrile-based polymer and its preparation method, the content of the second monomer in step 1) plays a crucial role in the super absorbent performance. In the present invention, the second monomer is an unsaturated olefin with a carboxylic acid group, which can be a carboxylic acid unsaturated olefin such as acrylic acid, itaconic acid or methacrylic acid. The concentration range of the carboxylic acid unsaturated olefin to the total monomer is between 1wt% and 13wt%, and the optimal range is between 2% and 8%. If the concentration is too low, the corresponding polymer has less carboxyl content, which affects the water absorption and grafting modification performance of the polymer; if the concentration is too high, it affects the polymerization reaction, and also causes high consumption of the second monomer and increases the cost. The total monomer concentration in the polymerization kettle ranges from 6wt% to 25wt%, and the optimal range is between 8wt% and 20wt%. When the monomer concentration is high, although the aqueous phase suspension polymerization water is easy to transfer heat as a medium, too high a monomer concentration is easy to cause "explosion", affecting normal production. Unsaturated olefin copolymers with carboxyl groups are easy to generate high molecular weight polymers, which affects the application of the polymer. Therefore, it is necessary to control the molecular weight of the polymer. The chain transfer agent generally adopts a hydroxyl-containing organic chain transfer agent, such as tetrahydroxyporphyrin, isopropanol, hydroxylamine, etc. The ratio of the chain transfer agent to the total monomer is between 0.5 and 4.5wt%. By adding graphene, a stably dispersed graphene aqueous solution is directly added to the aqueous phase suspension, so that the graphene is evenly dispersed in the suspension, copolymerized and modified, and the graphene accounts for 2%-10% of the total monomer, so that the polymer of the present invention has better conductive function.

[0033] The initiator system described in step 2) is a water-soluble oxidation / reduction system, and the types of oxidants include ammonium persulfate (APS), potassium persulfate (KPS), sodium chlorate, hydrogen peroxide, etc., and the types of reducing agents include sodium sulfite, sodium bisulfite, sulfurous acid, ethylenediamine, etc. The ratio of initiator to total monomers is between 0.5 and 4.5 wt%, preferably between 1.0 and 4.0%. Finally, a high molecular weight polymer with a molecular weight of 50,000 to 100,000 can be obtained.

[0034] The hot air drying described in step 5) is preferably carried out by heating with hot air containing nitrogen, and the heating temperature is controlled between 80 and 150°C, preferably between 90 and 120°C. Too high a temperature may easily cause oxidation of the polymer and yellowing; too low a temperature may not dry the polymer and cause powder agglomeration.

[0035] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0036] The functional polymer of the present invention has a molecular weight greater than 50,000 and a water absorption capacity greater than 2 times its own weight. At the same time, the polymer powder can provide abundant carboxylic acid groups and can be directly grafted and modified to prepare polymers with different functional groups without hydrolysis. Graphene is added to the polymer to have a conductive function.

[0037] The preparation method of the present invention directly performs water-phase suspension copolymerization modification to obtain a conductive acrylonitrile-based functional polymer material with super high water absorption and direct graft modification. By using a water-phase suspension polymerization method to treat more than 85% acrylonitrile and less than 15% unsaturated olefins with carboxylic acid groups, a high molecular weight polymer with a super water absorption function of more than 50,000 is obtained. In addition to the super water absorption function, the polymer can also be modified by grafting, cross-linking, etc. to generate modified polymers with different functional groups for use in different fields. Compared with the conventional PAN-based polymer or fiber hydrolysis currently used, the polymer or fiber obtained by water-phase suspension polymerization modification has more carboxylic acid groups and is evenly distributed, while the fiber strength is not affected and the performance is stable. DETAILED DESCRIPTION

[0038] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0039] The reagents used in the following examples can all be obtained through commercial sources.

[0040] Example 1

[0041] (1) In a 1L four-necked flask connected to a condenser and a mechanical stirring paddle, add 500 mL of deionized water, 57.6 g of acrylonitrile, and 6.4 g of itaconic acid, stir for 30 minutes under a nitrogen atmosphere to remove oxygen from the system, and keep the temperature at 25°C;

[0042] (2) Keeping the temperature constant, adjusting the pH value of the system to 2.0 with H2SO4 and NaOH, and monitoring the pH value of the solution system in real time during the reaction with a pH meter; adding 1.3 g of chain transfer agent diethylhydroxylamine and 400 mL of pure water; adding 0.6 g of ammonium persulfate (APS) and 2.4 g of ammonium bisulfite, a total of 3 g; adding 3 g of graphene, and carrying out polymerization reaction at 60 °C;

[0043] (3) The solution was mechanically stirred at 200 rpm by a stirrer, and the reaction system gradually became turbid. The reaction was stirred for 2 h to complete the reaction. An appropriate amount of 5 wt % NaOH solution was added to adjust the pH value of the polymerization suspension to 4.5 to terminate the reaction.

[0044] (4) The turbid liquid was filtered out, and the filter cake was rinsed with methanol and deionized water for multiple times to remove residual monomers and initiators. Finally, the filter cake was placed in a vacuum oven and dried for 24 hours to obtain a polymerization product.

[0045] Example 2

[0046] (1) In a 1L four-necked flask connected to a condenser and a mechanical stirring paddle, add 500 mL of deionized water, 108 g of acrylonitrile, and 12 g of itaconic acid, stir for 30 minutes under a nitrogen atmosphere to remove oxygen from the system, and keep the temperature at 25°C;

[0047] (3) Keeping the temperature constant, adjusting the pH value of the system to 2.5 with H2SO4 and NaOH, and monitoring the pH value of the solution system in real time during the reaction with a pH meter; adding 2.4 g of chain transfer agent diethylhydroxylamine and 300 mL of pure water; adding 1 g of potassium persulfate (APS) and 3.8 g of sodium bisulfite, a total of 4.8 g, adding 3.5 g of graphene, and carrying out polymerization reaction at 40 °C;

[0048] (4) The solution was mechanically stirred at 200 rpm by a stirrer, and the reaction system gradually became turbid. The reaction was stirred for 2.5 h to complete the reaction. An appropriate amount of 3 wt % NaOH solution was added to adjust the pH value of the polymerization suspension to 4.0 to terminate the reaction.

[0049] (5) The turbid liquid was taken out and filtered, and the filter cake was rinsed with methanol and deionized water for multiple times to remove residual monomers and initiators. Finally, the filter cake was placed in a vacuum oven and dried for 24 hours to obtain a polymerization product.

[0050] Example 3

[0051] (1) In a 1L four-necked flask connected to a condenser and a mechanical stirring paddle, add 500 mL of deionized water, 144 g of acrylonitrile, and 16 g of itaconic acid, stir for 30 minutes under a nitrogen atmosphere to remove oxygen from the system, and keep the temperature at 25°C;

[0052] (3) Keeping the temperature constant, adjusting the pH value of the system to 2.8 with H2SO4 and NaOH, and monitoring the pH value of the solution system in real time during the reaction with a pH meter; adding 3.2 g of chain transfer agent diethylhydroxylamine and 200 mL of pure water; adding 1.5 g of ammonium persulfate (APS) and 4.9 g of ammonium bisulfite, a total of 6.4 g, adding 4 g of graphene, and carrying out polymerization at 30 °C;

[0053] (4) The solution was mechanically stirred at 200 rpm by a stirrer, and the reaction system gradually became turbid. The reaction was stirred for 3 h to complete the reaction. An appropriate amount of 2 wt % NaOH solution was added to adjust the pH value of the polymerization suspension to 3.5 to terminate the reaction.

[0054] (5) The turbid liquid was taken out and filtered, and the filter cake was rinsed with methanol and deionized water for multiple times to remove residual monomers and initiators. Finally, the filter cake was placed in a vacuum oven and dried for 24 hours to obtain a polymerization product.

[0055] Example 4

[0056] (1) In a 1L four-necked flask connected to a condenser and a mechanical stirring paddle, add 500 mL of deionized water, 60.8 g of acrylonitrile, and 3.2 g of acrylic acid, stir for 30 minutes under a nitrogen atmosphere to remove oxygen from the system, and keep the temperature at 25°C;

[0057] (2) Keeping the temperature constant, adjusting the pH value of the system to a constant value of 2.0 with HNO3 and NaOH, and monitoring the pH value of the solution system in real time during the reaction with a pH meter; adding 0.64 g of chain transfer agent diethylhydroxylamine and 400 mL of pure water; adding 0.6 g of ammonium persulfate (APS) and 2.4 g of ammonium bisulfite, a total of 3 g, adding 5 g of graphene, and carrying out polymerization reaction at 60 °C;

[0058] (3) The solution was mechanically stirred at 200 rpm by a stirrer, and the reaction system gradually became turbid. The reaction was stirred for 2 h to complete the reaction. An appropriate amount of 5 wt % NaOH solution was added to adjust the pH value of the polymerization suspension to 4.5 to terminate the reaction.

[0059] (4) The turbid liquid was filtered out, and the filter cake was rinsed with methanol and deionized water for multiple times to remove residual monomers and initiators. Finally, the filter cake was placed in a vacuum oven and dried for 24 hours to obtain a polymerization product.

[0060] Example 5

[0061] (1) In a 1L four-necked flask connected to a condenser and a mechanical stirring paddle, add 500 mL of deionized water, 114 g of acrylonitrile, and 6 g of acrylic acid, stir for 30 minutes under a nitrogen atmosphere to remove oxygen from the system, and keep the temperature at 25°C;

[0062] (2) Keeping the temperature constant, adjusting the pH value of the system to 3.0 with HNO3 and NaOH, and monitoring the pH value of the solution system in real time during the reaction with a pH meter; adding 2.4 g of chain transfer agent diethylhydroxylamine and 300 mL of pure water; adding 1 g of potassium persulfate and 3.8 g of sodium bisulfite, a total of 4.8 g, adding 3.5 g of graphene, and carrying out polymerization reaction at 40°C;

[0063] (3) The solution was mechanically stirred at 200 rpm by a stirrer, and the reaction system gradually became turbid. The reaction was stirred for 2.5 h to complete the reaction. An appropriate amount of 3 wt % NaOH solution was added to adjust the pH value of the polymerization suspension to 4.0 to terminate the reaction.

[0064] (4) The turbid liquid was filtered out, and the filter cake was rinsed with methanol and deionized water for multiple times to remove residual monomers and initiators. Finally, the filter cake was placed in a vacuum oven and dried for 24 hours to obtain a polymerization product.

[0065] Example 6

[0066] (1) In a 1L four-necked flask connected to a condenser and a mechanical stirring paddle, add 500 mL of deionized water, 152 g of acrylonitrile, and 8 g of acrylic acid, stir for 30 minutes under a nitrogen atmosphere to remove oxygen from the system, and keep the temperature at 25°C;

[0067] (2) Keeping the temperature constant, adjusting the pH value of the system to 2.6 with HNO3 and NaOH, and monitoring the pH value of the solution system in real time during the reaction with a pH meter; adding 6.4 g of chain transfer agent diethylhydroxylamine and 200 mL of pure water; adding ammonium persulfate (APS) and ammonium bisulfite, a total of 6.4 g, adding 4.5 g of graphene, and carrying out polymerization reaction at 30°C;

[0068] (5) The solution was mechanically stirred at 200 rpm by a stirrer. The reaction system gradually became turbid. The reaction was stirred for 3 h to complete the reaction. An appropriate amount of 2 wt % NaOH solution was added to adjust the pH value of the polymerization suspension to 3.5 to terminate the reaction.

[0069] (6) The turbid liquid was filtered out, and the filter cake was rinsed with methanol and deionized water for multiple times to remove residual monomers and initiators. Finally, the filter cake was placed in a vacuum oven and dried for 24 hours to obtain a polymerization product.

[0070] Comparative Example 1

[0071] This comparative example is a method of preparing an acrylonitrile-based polymer containing a carboxylic acid group by hydrolysis in the prior art:

[0072] (1) Weigh 20 g of polymer powder or fiber obtained by copolymerization of acrylonitrile and methyl methacrylate (90:10);

[0073] (2) adding to a sodium hydroxide aqueous solution at 50° C. and having a pH value of 10, stirring to carry out a hydrolysis reaction;

[0074] (3) Maintaining temperature for 30 min, the polymer or fiber turns brown;

[0075] (4) After taking it out and cleaning it with pure water, put it into a dilute HNO3 aqueous solution, and control the pH between 2-3. The fiber will turn yellow;

[0076] (5) Take out the fiber, wash it with pure water and then dry it.

[0077] Application Examples

[0078] Determination of carboxyl content in polymers

[0079] Nicolet 6700 Fourier transform infrared spectrometer was used to characterize the group structure of PAN copolymers. The test method was potassium bromide tablet method, the scanning range was between 400–4000 cm-1, the spectral resolution was 4 cm-1, and the number of scans was 32 times. The carboxyl content can be calculated using the characteristic absorption bands of C=O of AA and C≡N of AN in the infrared spectrum. In order to reduce the error of physical changes, the optical density ratio (ODR) value needs to be calculated. ODR can be expressed as formula (1-1)

[0080]

[0081] Where I and Io represent the transmitted radiation and incident radiation intensities obtained from the infrared (IR) spectrum, respectively.

[0082] x=16.3y-8.5y2+2.24y3-1.78 (1-2)

[0083] Where x is the molar percentage of AA in the polymer and y is the ODR value. (Polymers. 2015; 7(7): 1205-1220.)

[0084] Table 1

[0085] Example Molecular weight / ten thousand Carboxyl content, % Water absorption, times Specific resistance (Ω·cm) 1 6 8.49 3.9 <![CDATA[7.6x10 9 ]]> 2 7.5 8.78 3.8 <![CDATA[7.1x10 9 ]]> 3 8 9.07 4.0 <![CDATA[6.8x10 9 ]]> 4 8 4.5 3.1 <![CDATA[6.4x10 8 ]]> 5 6.5 4.83 3.2 <![CDATA[5.8x10 9 ]]> 6 5 4.88 3.0 <![CDATA[2.8x10 9 ]]> Comparative Example 1 5 2.0 1.2 <![CDATA[9.1x10 12 ]]>

[0086] In Table 1, Examples 1 to 6 adopt the method of aqueous phase suspension copolymerization modification to prepare copolymers with a carboxyl content greater than 4%. Different feed ratios generate different polymer compositions, and the molecular weight of the polymer can be freely controlled by adjusting the chain transfer agent. The prepared polymer powder is white and has good water absorption, which is more than twice its own weight. The comparative example adopts hydrolysis and acid treatment to increase carboxylic acid and water absorption. After hydrolysis, the polymer or fiber appears yellow, but because it is only a surface modification, the increased carboxylic acid group is limited, the water absorption is not significantly improved, and it is not uniform. If the degree of hydrolysis is further increased in the comparative example, the polymer or fiber is directly in a paste state, which does not meet the strength requirements. Compared with the pure acrylonitrile polymer (Comparative Example 1) of the prior art, the graphene / acrylonitrile-based polymer prepared by the stock solution has a specific resistivity increase of 3-5 orders of magnitude.

[0087] The modified copolymer prepared by this patent can be made into fibers with active groups by wet spinning. After fiber grafting modification, it can be used for adsorption of heavy metals, ammonia and carbon dioxide. It can also be used in medical treatment as a water-absorbing conductive material.

[0088] The preferred embodiments of the present invention have been specifically described above, but the present invention is not limited to the embodiments. Those skilled in the art may make various equivalent modifications or substitutions without violating the spirit of the present invention. These equivalent modifications or substitutions are all included in the scope defined by the claims of this application.

Claims

1. A graphene / acrylonitrile-based functional high molecular polymer, which has good water absorption and electrical conductivity, and comprises the following components in weight percentage: a first monomer acrylonitrile accounts for 84%-97% of the total monomer ratio, a second monomer carboxyl-containing unsaturated olefin accounts for 1%-13% of the total monomer ratio, a chain transfer agent accounts for 0.5%-4.5% of the total monomer ratio, graphene accounts for 2%-10% of the total monomer ratio, and an initiator accounts for 0.5%-4.5% of the total monomer ratio.

2. The graphene / acrylonitrile-based functional polymer according to claim 1, characterized in that: The polymer comprises the following components in weight percentage: the first monomer acrylonitrile accounts for 88%-95% of the total monomer ratio, the second monomer unsaturated olefin containing carboxyl accounts for 2%-10% of the total monomer ratio, the chain transfer agent accounts for 1%-4% of the total monomer ratio, the graphene accounts for 3%-6% of the total monomer ratio, and the initiator accounts for 0.8%-4.0% of the total monomer ratio.

3. The graphene / acrylonitrile-based functional macromolecular polymer according to claim 1, characterized in that: The first monomer acrylonitrile is required to have an acrylonitrile content greater than 99.5% and an iron content less than 0.1 mg / kg.

4. The graphene / acrylonitrile-based functional macromolecular polymer according to claim 1, characterized in that: The second monomer, the unsaturated olefin containing a carboxyl group, is one or more of acrylic acid, itaconic acid or methacrylic acid.

5. The graphene / acrylonitrile-based functional macromolecular polymer according to claim 1, characterized in that: The chain transfer agent is one or more of isopropanol, diethylhydroxylamine or tetrahydroxyporphyrin.

6. The graphene / acrylonitrile-based functional macromolecular polymer according to claim 1, characterized in that: The initiator is a water-soluble oxidation / reduction system initiator, wherein the oxidant is ammonium persulfate, potassium persulfate, sodium chlorate or hydrogen peroxide; the reducing agent is sodium sulfite, sodium bisulfite, sulfurous acid or ethylenediamine; and the mass ratio of the oxidant to the reducing agent is 1:1 to 1:

6.

7. The graphene / acrylonitrile-based functional macromolecular polymer according to claim 1, characterized in that: The molecular weight of the super-high water-absorbent acrylonitrile-based polymer is between 50,000 and 100,000, and the water absorption capacity is more than twice its own weight.

8. The method for preparing the graphene / acrylonitrile-based functional macromolecular polymer according to any one of claims 1 to 7, comprising: 1) adding acrylonitrile, a first monomer, and a carboxyl-containing unsaturated olefin, a second monomer, into a polymerization kettle after being measured by a flow meter according to weight percentage; 2) Start the polymerization stirring, keep the temperature at 20°C to 30°C, add the chain transfer agent and pH adjuster, and adjust the pH of the mixed solution to 1.5 to 3.5; then add the initiator, carry out the polymerization reaction at 30-60°C, and control the reaction time to 2-3h to generate an acrylonitrile-based polymer suspension with a carboxylic acid group; 3) adding a stably dispersed graphene aqueous solution to the polymer suspension; 4) adjusting the pH value of the acrylonitrile-based polymer suspension to between 3.0 and 5.0 using an alkaline solution to terminate the polymerization reaction; 5) After the pH of the acrylonitrile-based polymer suspension is adjusted, the polymer forms a filter cake, and the filter cake is dried at 80-150° C. to obtain a super absorbent acrylonitrile-based polymer.

9. The preparation method according to claim 8, characterized in that: The total monomer concentration in the polymerization kettle in step 1) is in the range of 6 wt% to 25 wt%.

10. The preparation method according to claim 8, characterized in that: The pH regulator in step 2) is a regulating system of nitric acid or sulfuric acid and sodium hydroxide, and the pH of the mixed solution is adjusted to be in the range of 1.8 to 3.

0.

11. The preparation method according to claim 8, characterized in that: The alkaline solution in step 3) is an alkaline solution with a concentration of 1-8%. The alkaline substance can be ammonia water, caustic soda, potassium hydroxide, etc. The alkaline solution adjusts the pH value of the acrylonitrile-based polymer suspension to between 3.0 and 5.

0.

12. The preparation method according to claim 8, characterized in that: The drying in step 4) is carried out by heating and drying with hot air containing nitrogen, and the heating temperature is controlled between 90 and 120°C.